The IDH1 Mutation-Induced Oncometabolite, 2-Hydroxyglutarate, May Affect DNA Methylation and Expression of PD-L1 in Gliomas - Mu, Luyan; Long, Yu; Yang, Changlin; Jin, Linchun; Tao, Haipeng; Ge, Haitao; Chang, Yifan E.; Karachi, Aida; Kubilis, Paul S.; De Leon, Gabriel; Qi, Jiping; Sayour, Elias J.; et al. (Frontiers in Molecular Neuroscience, 2018)
Background: Malignant gliomas are heterogeneous brain tumors with the potential for aggressive disease progression, as influenced by suppressive immunoediting. Given the success and enhanced potential of immune-checkpoint inhibitors in glioma immunotherapy, we focused on the connections between genetic alterations affected by IDH1 mutations with immunological landscape changes. Methods: Paired, surgically resected tumors from lower-grade gliomas and glioblastomas were investigated, and a genetic analysis of patients’ primary tumor samples culled from TCGA datasets was performed. Results: The results demonstrate that when compared with IDH1-mutant tumors, IDH1 wildtype tumors represent an immunosuppression landscape and elevated levels of PD-L1 expression. DNA hypo-methylation of the PD-L1 gene, as well as gene and protein expression levels, were observed in the wildtype tumors. We also found that quantitative levels of IDH1 mutant proteins were positively associated with recurrence-free survival (RFS) rates. A key product of the IDH1 mutation (2-hydroxyglutarate) was found to transiently increase DNA methylation and suppress PD-L1 expression. Conclusions: IDH1 mutations impact the immune landscape of gliomas by affecting immune infiltrations and manipulating checkpoint ligand PD-L1 expression. Applications of immune checkpoint inhibitors may be beneficial for chemoradiation-insensitive IDH1-wildtype gliomas.